Acordo de quotistas: o contrato parassocial na sociedade limitada - Carmen Godoy Vieira de Souza (2011)
The Shareholders Agreement is a legal instrument common used in the social practice of the Limited Liability Companies. The absence of regulation of this institute provokes questions about its validity. Thus, the modest legal literature and judicial decisions, on the business relations prevails the legal uncertainty, which discourages economic investments in Brazil, weakening the firm and making the society to pay more. Thereby, the main purpose of this scientific work is to proceed on a examination of the legal nature of the Shareholders Agreement, through the investigations on the principles and laws inside the Brazilian legal system, and also the investigation of the business practices, in order to demonstrate the validity of the Shareholders Agreement on the Limited Liability Companies, based on the theoretical construction of the institute of collateral agreements. The preponderance of the Limited Liability Companies in the Brazilian economic context shows the necessity of recognize its validity and understand the Shareholders Agreement, so its use would be productive to the firm and the society, making the relationship between the partners stronger and enabling the reduction of the transaction costs.